2013
DOI: 10.1021/nn4034794
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology in Plant Disease Management: DNA-Directed Silver Nanoparticles on Graphene Oxide as an Antibacterial against Xanthomonas perforans

Abstract: Bacterial spot caused by Xanthomonas perforans is a major disease of tomatoes, leading to reduction in production by 10–50%. While copper (Cu)-based bactericides have been used for disease management, most of the X. perforans strains isolated from tomatoes in Florida and other locations worldwide are Cu-resistant. We have developed DNA-directed silver (Ag) nanoparticles (NPs) grown on graphene oxide (GO). These Ag@dsDNA@GO composites effectively decrease X. perforans cell viability in culture and on plants. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
247
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(256 citation statements)
references
References 35 publications
7
247
0
2
Order By: Relevance
“…13 Our previous study showed also that GO and silver nanowire composites could have improved antibacterial activity with better cell compatibility. 15 In addition, Zhang et al reported that graphene had a positive impact on promoting seed germination and seedling growth of tomatoes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…13 Our previous study showed also that GO and silver nanowire composites could have improved antibacterial activity with better cell compatibility. 15 In addition, Zhang et al reported that graphene had a positive impact on promoting seed germination and seedling growth of tomatoes.…”
Section: Introductionmentioning
confidence: 93%
“…Especially silverbased antibacterial agents have been widely studied due to their good antibacterial activity. 13,14 In our previous studies, we prepared some silver-based composites with graphene oxide (GO), 15 silicon oxide nanospheres, 16 and porous carbon. 17 These nanocomposites showed excellent antibacterial activity against Escherichia coli and Xanthomonas oryzae pv.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, NP-GO NCs exhibit enhanced surface enhanced Raman scattering, catalytic, and antibacterial properties compared to bare GO and NP. [208][209][210][211][212][213] Recent studies reported the fabrication of AgNPs-decorated GO as an effective antibacterial agent. [213][214][215][216] Synthesis of AgNPs decorated on magnetic GO NCs was demonstrated, which showed highly effective inhibitory property and reusability even at the very low concentration (12.5 ppm).…”
Section: Synthesis Of Agnps By Proteins and Dnamentioning
confidence: 99%
“…Song et al 15 synthesized the silver/polyrhodanine compositedecorated silica nanoparticles, which exhibited excellent antimicrobial activity toward Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) because of the antibacterial effects of both the silver nanoparticles and the polyrhodanine. Tan et al 16 synthesized antibacterial Ag@dsDNA@GO, which can wrap around the Xanthomonas perforans cell and results in rapid cell apoptosis, showing the synergistic antibacterial effect. While these nanostructures can effectively enhance the antibacterial activity of Ag NPs, they oen require complex and tedious preparation methods, and suffering from low yields, poor longterm antibacterial activity, and biocompatibility problems.…”
Section: -14mentioning
confidence: 99%